STATE OF PREVENTIVE WORK AMONG THE POPULATION THROUGH THE PRISM OF A SOCIOLOGICAL SURVEY OF MEDICAL WORKERS - Shafranskyi, V.V. (World of Medicine and Biology, 2018)
At the end of last century, the strategy of health promotion began to be actively implemented in the world. The emergence of this concept has led to changes in the socio-economic life of society, as well as certain trends in the development of the health care system. At the forefront were chronic diseases, the emergence and treatment of which is largely due to the conditions of human life and its behavior. Development of medical technologies and development of new drugs have led to an accelerated growth in demand for medical services than to improve the health of the population. Therefore, the relationship between the socio-economic environment of life, lifestyle, on the one hand, and the state of health - on the other, became perceived not only by medical specialists, but also by politicians, society. The European Action Plan for Strengthening Public Health Capacities and Services defines ten key operational public health functions, one of which is disease prevention, which includes early detection of health disorders. Proceeding from the above, we were asked to study the state of preventive work among the population, its role and place in the activities of the physician; possibilities of conducting; the attitude of health workers to preventive work; the quality and consequences of this work among the population over the last years. The group of participants in the sociological survey consisted of 340 medical doctors – health care organizers, 356 medical doctors - general practitioners and 201 medical doctors at the secondary and tertiary levels of health care. In total, 897 respondents from nine regions of our country took part in the study. A special questionnaire was developed for conducting a sociological survey among medical staff, which respondents filled in online or on paper. The data obtained during the sociological study were processed statistically. In conducting the comparison, the criterion of the hi-square with the Jeet’s correction is used. The first step of the study was to study the results of the respondents’ assessment of the possibility of conducting preventive work among the population. The next step of the study was to study the results of the respondents’ assessment of health and lifestyle and the relation to personal health of the population as a whole and patients directly. After analyzing the whole array of data obtained, we have established that the modern health care system of the country does not contribute to the prevention of diseases among the population. Much of the medical staff is deprived of the opportunity to carry out preventive work among the population. For the last three years, the health status, lifestyle and the public’s relation to personal health have deteriorated. The vast majority of citizens do not have a personal health priority, and this does not contribute to its improvement. At the same time, during the last decades in the highly developed countries of the world due to state policy aimed at creating the necessary conditions for the wide introduction of various forms of motor activity in the daily life in their organic combination with rational nutrition, the fight against harmful habits and the improvement of environmental ecology, mortality people of young and middle age has decreased several times, the average life expectancy has increased by 10-20 years, sharply increased the viability of the population, which is crazy in fact, ensured a significant economic growth of countries. In scientific studies it is convincingly shown that in the prevention of chronic non-infectious diseases, all possibilities of medical medicine are 5-6 times lower than the efficiency of factors of a healthy lifestyle. Thus, the development of a modern public health system in our country, based on the strategy of "health promotion" and the best world experience on the implementation of ten main operational functions of public health, will improve the health of the population, improve quality and prolong life expectancy citizens of our state.